2018
DOI: 10.1002/acr.23446
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Experience With Off‐Label Use of Interleukin‐1 Targeting Treatment in Familial Mediterranean Fever Patients

Abstract: Anti-IL-1 treatment is an effective alternative for controlling attacks and decreasing proteinuria in colchicine-resistant FMF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 20 publications
3
40
0
7
Order By: Relevance
“…Another Varan et al showed that anti-IL1 treatments significantly reduced the amount of proteinuria (from 1606 mg/day to 519 mg/day) [14]. Moreover, national data that was collected with 172 subjects demonstrated a significant decrease in proteinuria (5458.7 mg/24 h before and 3557.3 mg/24 h after) [9]. Instead, in these studies, patients were not sub-grouped, and their data was not analyzed regarding their GFR.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another Varan et al showed that anti-IL1 treatments significantly reduced the amount of proteinuria (from 1606 mg/day to 519 mg/day) [14]. Moreover, national data that was collected with 172 subjects demonstrated a significant decrease in proteinuria (5458.7 mg/24 h before and 3557.3 mg/24 h after) [9]. Instead, in these studies, patients were not sub-grouped, and their data was not analyzed regarding their GFR.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies have demonstrated the efficiency of these treatments. Akar et al reported the response rate as 76.5% in the anakinra group and 67.5% in the canakinumab group in a total of 172 colchicine-resistant patients [9]. In the study by Kucuksahin et al, anti-IL-1 treatments significantly decreased the number of attacks in 26 colchicine-resistant patients with FMF.…”
Section: Discussionmentioning
confidence: 97%
“…Biological therapies to treat FMF have been recently reviewed and include anakinra, an IL-1 receptor antagonist; rilonacept, a dimeric fusion protein that blocks the IL-1 receptor; and canakinumab, a human monoclonal anti-IL-1β antibody [55]. Recent studies in FMF patients with colchicine resistance have shown a significant reduction in attack frequency with anakinra or canakinumab [56,57], with a complete response up to 16 weeks of~70% for canakinumab [58]. Other agents that have been considered but with limited evidence to date include etanercept, a fusion protein targeting the tumour necrosis factor-α receptor; infliximab, a chimeric monoclonal antibody to TNF-α [59]; tocilizumab, a humanized monoclonal antibody targeting the IL-6 receptor [60]; and tofacitinib, a Janus kinase inhibitor [61].…”
Section: An Argument For Biologically-informed Treatmentmentioning
confidence: 99%
“…Подобные случаи -не редкость, у пациентов с FMF при-ступы лихорадки при приеме колхицина сохраняются в 30-45% случаев. В то же время назначение ингибиторов ИЛ1 у 42% пациентов с FMF приводит к полному контролю забо-левания, а в остальных случаях примерно в семь раз снижает частоту приступов лихорадки и более чем в полтора раза про-теинурию [40]. Основные принципы лечения АВЗ, сформи-рованные на основании анализа данных литературы в рамках инициативы EUROFEVER, предполагают применение у па-циентов с плохо контролируемыми MVKD, TRAPS, PAPA и FMF в качестве прпаратов выбора ингибиторов ИЛ1 или ФНОα [41].…”
Section: криопирин-ассоциированные периодические синдромыunclassified